Rethinking relationships - Duck, Steve; SAGE Knowledge (Online service). (Los Angeles, Calif. Sage, 2011)
"In this book, Steve Duck, a founder of and prolific crossdisciplinary contributor to the field of relationships research, challenges students to re-examine their assumptions about relationships. Duck shows that in order to understand relationships properly, students must understand the roles that society, language, our taken-for-granted assumptions, and other people who share those assumptions play in the conduct of relationships."-Provided by publisher.
Old and new ways of seeing relationships -- Personal and social orders : relating, meaning, and talking -- What has personality got to do with relationships? -- The bodily materiality of relating -- Sense and sensuality : the relationship between sexual activity and knowledge of the world -- Wealth, place, gifts, and rituals : the material structures and practices of relational experience -- The language of relationships in a social order -- Talk and speaking personal orders.
Includes bibliographical references and index.
Keywords: Interpersonal relations; Interpersonal communication; Electronic books